Lemna minor exposed to fluoranthene: growth, biochemical, physiological and histochemical changes - Zezulka, Stěpán; Kummerová, Marie; Babula, Petr; Váňová, Lucie (Aquatic toxicology (Amsterdam, Netherlands), 2013)
Polycyclic aromatic hydrocarbons (PAHs) represent one of the major groups of organic contaminants in the aquatic environment. Duckweed (Lemna minor L.) is a common aquatic plant widely used in phytotoxicity tests for xenobiotic substances. The goal of this study was to assess the growth and the physiological, biochemical and histochemical changes in duckweed exposed for 4 and 10 days to fluoranthene (FLT, 0.1 and 1 mgL(-1)). Nonsignificant changes in number of plants, biomass production, leaf area size, content of chlorophylls a and b and carotenoids and parameters of chlorophyll fluorescence recorded after 4 and 10 days of exposure to FLT were in contrast with considerable changes at biochemical and histochemical levels. Higher occurrence of reactive oxygen species (ROS) caused by an exposure to FLT after 10 days as compared to control (hydrogen peroxide elevated by 13% in the 0.1 mgL(-1) and by 41% in the 1 mgL(-1) FLT; superoxide anion radical by 52% and 115% respectively) reflected in an increase in the activities of antioxidant enzymes (superoxide dismutase by 3% in both treatments, catalase by 9% and 1% respectively, ascorbate peroxidase by 21% and 5% respectively, guaiacol peroxidase by 12% in the 0.1 mgL(-1) FLT). Even the content of antioxidant compounds like ascorbate (by 20% in the 1 mgL(-1) FLT) or total thiols (reduced forms by 15% in the 0.1 mgL(-1) and 8% in the 1 mgL(-1) FLT, oxidized forms by 36% in the 0.1 mgL(-1) FLT) increased. Increased amount of ROS was followed by an increase in malondialdehyde content (by 33% in the 0.1 mgL(-1) and 79% in the 1 mgL(-1) FLT). Whereas in plants treated by the 0.1 mgL(-1) FLT the contents of total proteins and phenols increased by 15% and 25%, respectively, the 1 mgL(-1) FLT caused decrease of their contents by 32% and 7%. Microscopic observations of duckweed roots also confirmed the presence of ROS and related histochemical changes at the cellular and tissue levels. The assessment of phytotoxicity of organic pollutant in duckweed based only on the evaluation of growth parameters could not fully cover the irreversible changes already running at the level of biochemical processes.
Keywords: Histology; thiobarbituric acid reactive substances; glutathione; Enzymes; reaktivní formy kyslíku; natural product reagent; FLT; PAH fluoranthene; fluoreny; DTNB; catalase; TCEP; SOD; guaiacol peroxidase; MDA; dithio-bis-nitrobenzoic acid; AO; polycyclic aromatic hydrocarbon(s); peroxidace lipidů; APX; Chlorophyll fluorescence; TBARS; Evan’ s blue; ROS; fluoranthene; nitro blue tetrazolium; biologické pigmenty; Reactive Oxygen Species; biomasa; dihydroethidium; Araceae; časové faktory; tris(2-carboxyethyl)phosphine; acridine orange; Pigments, Biological; Steinberg medium; ascorbate peroxidase; AsA; NBT; NPR; reduced ascorbic acid; Fluorenes; PAH(s); SM; GLU; Water Pollutants, Chemical; GPX; reactive oxygen species; superoxide dismutase; malondialdehyde; Biomass; CAT; DHE; Lemna minor L.; Time Factors; EB; Lipid Peroxidation; chemické látky znečišťující vodu